Perkecambahan Asimbiotik Biji Anggrek Dendrobium bicaudatum pada Media dengan Penambahan Ekstrak Tomat secara In Vitro - NI WAYAN SURIANTARI; IDA AYU PUTRI DARMAWATI; HESTIN YUSWANTI (Agrotrop : Journal on Agriculture Science, 2022)
Asymbiotic Germination of Dendrobium bicaudatum Orchid Seeds on Media with In Vitro Addition of Tomato Extract. Dendrobium bicaudatum is a natural orchid that needs to be preserved. Orchid seeds propagation naturally (symbiotic) has a low success rate. Orchid seeds do not have an endosperm. Asymbiotic germination with in vitro culture techniques can be an alternative solution for the propagation of orchid seeds. This study aimed to determine the effect of giving tomato extract on modified media on the asymbiotic germination of Dendrobium bicaudatum orchid seeds. This research used the Completely Randomized Design with five treatments of tomato extract concentration, namely 0%, 5%, 10%, 15%, 20%, with 4 replications. The variables observed in this study were the time and percentage of phase 1; time and percentage of phase 2; time and percentage of phase 3; time and percentage of phase 4; time and percentage of phase 5; and time and percentage of phase 6. The results showed that the tomato extract treatment had a significant or very significant effect on the germination of Dendrobium bicaudatum orchid seeds and the best treatment for the fastest and the highest percentage of germination from protocorm to First Leaf Primodium was the addition of tomato extract with a concentration of 15% or 20%, and a concentration of 0% tomato extract for the early stages of swelling of the embryo.